2019
DOI: 10.1111/jgh.14625
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of rescue bismuth quadruple therapy failure for Helicobacter pylori eradication

Abstract: Background and Aim Failure of bismuth quadruple therapy for Helicobacter pylori eradication is frequently observed. To increase the eradication rate, comprehensive analyses need to be performed regarding risk factors of bismuth quadruple therapy failure based on complete standard culture and antimicrobial susceptibility testing results. Methods Patients with history of failed first therapy who had H. pylori colonies isolated from culture and successful minimum inhibitory concentration (MIC) test were enrolled.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Since H pylori resistance to amoxicillin and tetracycline is uncommon, the explanation for the heterogeneous results could be that both amoxicillin and tetracycline are weak against H pylori or there is a possible antagonistic effect . Recent studies have suggested that a high level of resistance to metronidazole, at an MIC >32 μg/mL, could be a reliable predictor of eradication failure of bismuth‐containing quadruple therapy . In addition, other salvage regimens are needed in patients with high‐level metronidazole resistance for customized tailored therapy through antibiotic susceptibility tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since H pylori resistance to amoxicillin and tetracycline is uncommon, the explanation for the heterogeneous results could be that both amoxicillin and tetracycline are weak against H pylori or there is a possible antagonistic effect . Recent studies have suggested that a high level of resistance to metronidazole, at an MIC >32 μg/mL, could be a reliable predictor of eradication failure of bismuth‐containing quadruple therapy . In addition, other salvage regimens are needed in patients with high‐level metronidazole resistance for customized tailored therapy through antibiotic susceptibility tests.…”
Section: Discussionmentioning
confidence: 99%
“…The range of concentrations for tetracycline and metronidazole was from <1 to >16 μg/mL and <2 to >32 μg/mL, respectively. Resistance breakpoints for amoxicillin, metronidazole, and tetracycline were defined as ≥0.5, ≥8, and ≥1 μg/mL, respectively . The breakpoint for tetracycline resistance was used according to EUCAST guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Bismuth‐containing quadruple therapy exhibits a high eradication rate, even in the presence of antibiotic resistance . Although resistance rate to metronidazole is over 30% in Korea, bismuth‐containing quadruple therapy is effective unless the minimum inhibitory concentration (MIC) of metronidazole exceeds 32 μg/mL . Furthermore, H. pylori resistance against tetracycline has been low and stable in Korea for the past 16 years .…”
Section: Introductionmentioning
confidence: 99%
“…The current study by Lee et al . has taken this further to assess the level of metronidazole resistance with pretreatment MIC level . Results of this study suggest that low level (MIC 8–32 μg/mL) of metronidazole resistance can still be successfully treated by bismuth quadruple therapy.…”
mentioning
confidence: 96%
“…In this issue of the Journal of Gastroenterology and Hepatology , Lee et al . have presented their works on investigating risk factors for failure using rescue bismuth quadruple therapy . The authors have enrolled 54 patients who failed first‐line therapy and had H .…”
mentioning
confidence: 99%